Bala de gelatina com colágeno hidrolisado e microcápsulas de maracujá (Passiflora edulis) - Machado, Celestina Tojal (2020)
The sour or yellow passion fruit (Passiflora edulis) is a tropical fruit rich in bioactive compounds and with characteristic acidity, flavor and aroma, with interesting insertion in foods, with limited use of acids, dyes and flavorings. Vitamin C is considered an important compound for maintaining cellular tissues, and contributes to the formation of collagen. The growing demand for healthy products that act in the prevention of diseases, encourage research on food characterization and innovation in food products with new ingredients. Therefore, the candy and confectionery industry needs to apply natural ingredients, following global trends. In this context, this work aimed to produce a product with preservation of bioactive compounds, through the encapsulation by ionic gelation of passion fruit juice, and the availability of proteins. To obtain the microcapsules, ionic gelation was performed with sodium alginate solution to obtain the product. And the candies were made in two formulations: gelatin candies with hydrolyzed collagen and passion fruit microcapsules, and gelatin candies with hydrolyzed collagen and passion fruit. The mints were stored at 5 ± 1ºC for 12 days, carrying out the analysis of soluble solids (ºbrix), titratable acidity, pH, total proteins, hydroxyproline, proline, bioactive compounds and antioxidant capacity (DPPH, ABTS and FRAP). The analyzes were performed in triplicate, with the data analyzed by ANOVA and the averages compared using the Tukey test at the level of 5% of significance. In the physical and chemical characterization of the passion fruit pulp and microcapsules, the significant difference (p≤ 0.05) prevailed in the analyzed parameters. In storage, evaluating the total protein content of samples of gelatine candy with microcapsules and control candy, differed significantly (p≤ 0.05). And, in relation to the storage time, the total protein contents of the two bullets evaluated, differed statistically (p≤ 0.05), but there was a gradual increase in the protein values. In the hydroxyproline parameter, the two samples studied showed statistical divergence between them (p≤ 0.05), indicating the preliminary contents of 2.67 g of Hydroxyproline / 100g of sample and 3.89 g of Hydroxyproline / 100g of sample, respectively. The levels of proline in the samples of gelatin candy with microcapsules and control candy, showed a significant difference (p≤ 0.05) between them, and the control candy presented higher values of proline rate when compared to the candy with microcapsules. And during storage, the investigated samples showed a significant reduction (p≤ 0.05) of proline values. The bullets proved to be a safe food, and did not show contamination by microorganisms. With the results exposed in this work, it can be concluded that the product obtained reveals an innovative potential, free of sugars, with the insertion of natural dye, and consisting of hydrolyzed collagen, presenting the structural amino acids (hydroxyproline and proline).